2004
DOI: 10.1161/01.hyp.0000148459.25908.49
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin: A Protective Mediator of Cardiac Fibrosis?

Abstract: O steopontin (OP) is a multifunctional cytokine and adhesion protein that contains an RGD (argininglycin-aspartate) binding sequence that enables it to interact with several integrins, CD44 variants, and other adhesion receptors. OP receptor binding then directly or indirectly activates intracellular signaling pathways, mediating its effects on cell-matrix and cell-cell interactions. OP is increased in response to pro-inflammatory cytokines and mechanical strain in various cell types, 1 and the function of its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
1
8
0
1
Order By: Relevance
“…Therefore, the liver response to damage in osteopontin-deficient mice appears quite distinctive. However, similarly to our data in liver, it has been recently suggested that osteopontin could be a protective mediator of cardiac fibrosis [33]. The mechanism of CCl 4 -induced fibrogenesis involves a toxicity of this compound for hepatocytes whereby CCl 4 induces hepatocyte necrosis following its metabolism to a toxic metabolite [34].…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, the liver response to damage in osteopontin-deficient mice appears quite distinctive. However, similarly to our data in liver, it has been recently suggested that osteopontin could be a protective mediator of cardiac fibrosis [33]. The mechanism of CCl 4 -induced fibrogenesis involves a toxicity of this compound for hepatocytes whereby CCl 4 induces hepatocyte necrosis following its metabolism to a toxic metabolite [34].…”
Section: Discussionsupporting
confidence: 88%
“…Increased HA causes an aggressive phenotype leading to severe lung fibrosis after bleomycin-induced injury38. OPN is an immobilized matrix phosphorylated glycoprotein39 that plays a key role in diabetic nephropathy40. The transfection of OPN siRNA in vivo inhibited the progression of chronic allograft nephropathy41.…”
Section: Discussionmentioning
confidence: 99%
“…Increased HA also produced an aggressive phenotype leading to severe lung fibrosis and death after bleomycin-induced injury [43]. OPN is a phosphorylated glycoprotein that exists as an immobilized matrix protein and a cytokine [45]. Recent evidence suggests that OPN plays a key role in fibrosis [46], [47].…”
Section: Discussionmentioning
confidence: 99%